Hemosiderotic fibrohistiocytic lipomatous lesion: case report and review of the literature - Ramalho, Antônio Roberto Oliveira; Nunes, Marcella Nara; Adad, Sheila Jorge; Leitão, Sebastião Almeida; Micheletti, Adilha Misson Rua (São Paulo Medical Journal, 2009)
CONTEXT: Lesions of the adipose tissue are the most common type of soft-tissue lesion among adults. CASE REPORT: We describe the case of a 33-year-old female patient with a soft-tissue lesion in her left knee that was diagnosed as a hemosiderotic fibrohistiocytic lipomatous lesion. This type of lesion, which was described for the first time in 2000, preferentially affects the ankle region of middle-aged women with a history of previous local trauma. Lesion recurrence is common, caused by incomplete resection, although there have not yet been any reports of metastases. After a review of the literature, we describe the clinical, radiological, morphological and immunohistochemical characteristics, along with their main differential diagnoses.